Virtual Reality Practice, Computer Games, and Improvement of Cerebral Palsy Balance: A Single Subject Study - Boroumand, Samira; Hassani Mehraban, Afsoon; Dadgou, Mahdi; Raji, Parvin (Journal of modern rehabilitation (Online), 2017)
Introduction: Virtual reality is a novel technology which creates attractive environment using computer hardware and software. In these virtual realities people can actively participate and use their motor and cognitive abilities. Current study aimed at investigating effect of virtual reality on the balance of children with cerebral palsy. Material and Methods: This research is a single subject study with ABA design conducted on three children with cerebral palsy (GMFCSΙ level). Basic phase and intervention phase of investigation lasted for 2 and 4 weeks, respectively. Intervention sessions were repeated 3 times per week like base line phase. In each intervention session, children performed different computer games for 21 minutes. These games require center of pressure displacement in the frontal and sagittal planes. Follow-up phase was implemented 2 to 3 months after completion of intervention phase. Changes were measured using following measurement tools: pediatric reach test (PRT), Timed Up and Go (TUG), 10-meter walking (10MW) and subtest of balance and lower limb strength test, including Bruininks-Oseretsky of Motor Proficiency (BOMP). Finally results were investigated using visual analysis and C Statistics. Results: Comparison of PRT tests and subtest of balance and lower limb strength test, including BOMP suggested significant improvement in static balance (P=0.000), jumping ability, and dynamic balance of children participating in the research and durability of this improvement in follow-up phase, though investigation of TUG and 10MW test results showed no significant improvement. Conclusion: Results in this research showed that using virtual reality can improve balance in children with cerebral palsy.